Education 4.0 in English for Survival Class: What, why, and how is to promote it? - Anggraeni, Candradewi Wahyu (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The purposes of this study are to explore the ways in promoting Education 4.0 in English for Survival class, to contend the reasons of promoting Education 4.0, and to discover the studentsâ viewpoints toward the use of Whatsapp and Instagram platforms for promoting Education 4.0. The research method used in this study is a qualitative approach in the form of case study. The participants of this study are the students and lecturer of English for Survival class. The instruments of data collection are observation, interview, and teaching reflexive log. The findings show that there are three ways in promoting Education 4.0, seven reasons of promoting Education 4.0, and two different studentsâ perspectives of promoting Education 4.0 in English for Survival class. In addition, the students and lecturer need to consider several aspects in promoting Education 4.0 in English Language Teaching.